Advances in Limnogeology: The lake‐basin‐type model revisited 25 years after…anomalies, conundrums and upgrades - Benavente, Cecilia Andrea (2024)
The lake-basin- type model classified the stratigraphic record of ancient lake sys-tems according to rates of potential accommodation relative to sediment + watersupply. The model convolved all modes and paths of water supply (direct fall,surficial, subsurface) with amounts and types of sediment supply (clastic, bio-genic, chemical) into a single basin-filling volume term (sediment + water); itsmajor strength was its widespread applicability. This was supported by subsequentinvestigations confirming the utility of this approach, but it also revealed someimportant limitations due to simplifications in the original model. The modelhas been expanded here to address all inland waters (lakes, ponds, wetlands, pla-yas) as well as adding two major subdivisions of the sediment + water term: (1)water supply paths and (2) the volume of water supply relative to sediment sup-ply. Water supply flow paths in the subsurface are subdivided into ‘throughflow’,‘recharge’ and ‘discharge’. Each of these groundwater hydrology states can be de-fined quite precisely by the ratio of net outflow to inflow, from persistently opento consistently closed. These paths can be deciphered using stable carbonate andoxygen isotope composition of primary lacustrine limestones, detailed sedimen-tology, stratigraphy, palaeontology and mineralogy. Distinguishing water supplypaths provides additional insights into playa systems and the occurrence andcharacter of evaporites and carbonates. The volume ratio of water to sedimentsupply most directly influences the water depths of lakes, ponds and wetlands,which affect water body hydrodynamics and ecosystem behaviour as well as thedetails of stratal stacking and depositional sequences. It helps fine-tune estimatesof the distribution of sediment texture, bedding, composition and organic mattercontent. The aim of this contribution is to address questions about the funda-mental types of inland water bodies and to explain the new lake-basin subtypesand provide examples that illustrate their potential to enable higher-resolution,robust analysis of inland water systems and their stratigraphic records.